Calcium intake in the Moroccan adolescents - El-houcine Sebbar; Hicham Sam; Ennouamane Saalaoui; Mohammed Choukri (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2017)
Purpose: Calcium needs vary in function with age, sex and individuals. Needs are increased in adolescents. The aim of our work is to evaluate the calcium intake in the Moroccan adolescents.                                                                                                                                       Methods: The version translated into Arabic dialect Fardellone questionnaire is tested on a sample of 257 Moroccan adolescents aged between 14 and 17 years old. Results: The study population includes 43% female (n = 111), 57% of male (n = 146). The mean calcium intake was 5991 mg per week, a daily consumption of 855 mg per day. The assessment of calcium intake showed a deficiency, and the average consumption of calcium per day is significantly lower than the recommended daily amount for this population. The comparison of both gender found a deficit higher among females than males. Conclusion: Evaluation of the calcium intake is an essential tool for better management of metabolic bone diseases.